Chemical concentrations of REE and Pb for Mn crusts from the Line Islands Archipelago - Andrew C Aplin (PANGAEA, 2023)
Mn crust samples were taken from dredge hauls collected at 16 sites by the Hawaii Institute of Geophysics. They are located along the Line Islands Archipelago between 15°S and 17°N, and from depths between 1150 and 4700 m. Each sample was analysed for La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Er, Yb, and Lu on the Kings College (London) inductively coupled plasma (IPC) spectrophotometer. Following digestion with a mixture of hydrofluoric and perchloric acid, residues were taken up in HCl and the REE isolated by means of cation exchange. The REE were converted to nitrates in concentrated HNO3 and analysed in a 2N HNO3 matrix. The levels of accuracy were determined by comparison with Kings College standards and were found to be better than -+ 6% for all elements except Pr and Lu (+ 9%). Precision was better than + 1% for all 11 elements. In addition, phosphorous was determined by ICP spectrophotometry at Imperial College.